The application of the organizational learning perspective in explaining the government's internal auditor’s role development - Wisdana, Monika Yustia; Winardi, Rijadh Djatu; Halim, Abdul; Frendy (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2024)
The management of mineral and coal non-tax state revenue (PNBP Minerba) requires urgent attention and improvement, which can be achieved through appropriate oversight of internal auditors. This study assesses the efficacy of internal audit role development through an organizational learning perspective. Authors interviewed eleven informants from internal auditors of the inspectorate and auditees from the Ministry of Energy and Mineral Resources (KESDM) of the Republic of Indonesia. The data corroborates our theoretical framework within organizational significance theory, which states that the interconnection of the relationship between internal auditors and auditees, the internal audit process, and internal auditor resources culminates in the "results zone." Within this zone, internal audits yield effective outcomes that can positively influence the organization’s significance. This research reveals that auditees feel that an internal auditor’s findings and recommendations can influence their organization. This perspective can enhance PNBP Minerba management system and foster learning and organizational change. However, internal auditor recommendations have not effectively spurred organizational learning in KESDM, implying that KESDM is still in the developmental phase. This study stands out for its qualitative exploration of organizational characteristics, particularly the interplay between internal auditors and auditees, the internal audit process, and internal auditor resources.